Legal Consequences of The Implementation of Reimbursement of Rights or Subrogation in Credit Activities - Riri Rayhan Abdul Azis (Estudiante Law Journal, 2021)
This researchaims to find out and analyze the legal consequences and inhibiting factors arising from the Implementation of Reimbursement of Rights or Subrogation in Credit Activities according to  the provisions of the Kitab of the Civil Law.  This research uses a sociological or empirical type of research with a qualitative approach.  The resultsof this study show that the legal consequences arising in  the implementation of reimbursement of rights or subrogation in credit activities cause losses to the creditor due to the implementation of subrogation not running properly and resulting in a blacklist to the debtor and to third parties who do not carry out their obligations.  Internal inhibiting factors are in the form of lack of information from the bank related to subrogation, also debtors often do not understand repayments and the absence of good faith from debtors while the inhibiting factors faced externally are in the form of third parties who pledge a decrease in economic capabilities,  lack of knowledge of third parties related to the existence of subrogation procedures  and the absence of good faith on the part of the third party in settling the remaining credit payments.